PENGAWASAN BADAN PENDAPATAN DAERAH TERHADAP PEMUNGUTAN PAJAK BUMI DAN BANGUNAN (PBB) DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2015 - Atmasepa, Dieka Tri; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Controlling is a procedure that really important for some work, especially in government. Less of controlling is a phenomenon that affect deviation and bad thing that makes disadvantageous for some parties, this phenomenon occurs in Kelurahan Simpang Baru Kecamatan Tampan , Pekanbaru City, which is the effectifities of controlling from Badan Pendapatan Daerah about collection regional income tax isn’t maximal, because there’s so many problem about the implementation of Badan Pendapatan Daerah that not going properly by the rules itself. Writer want to knows deeper about controlling from Badan Pendapatan Daerah about collection regional income in Kelurahan Simpang Baru, Pekanbaru City.The Purpose of this research is to know about the controlling from Badan Pendapatan Daerah Pekanbaru City for collection regional income tax, and to know about factors that affect the controlling that doing by Badan Pendapatan Daerah Pekanbaru City. This research method is qualitative descriptive, and types of data for this research are primer data and sekunder data.The result for this research is controlling from Badan Pendapatan Daerah about the collection regional income tax in Kelurahan Simpang Baru Kecamatan Tampan, Pekanbaru City isn’t maximal. So from this research , the conclusion are : (1) the implementation about controlling for regional income tax can be seen from all indicators , make a standar for controlling, take an assestment action , and take some correction action which is all of them are not going properly. (2) the factors that affect controlling from Badan Pendapatan Daerah for collection regional income tax in Kelurahan Simpang Baru Kecamatan Tampan Pekanbaru City can be seen from all indicators, human resource, facility, people participation and all of them are not going properly. The main problem is the human resource itself, lack of personil that have to controls many objective tax and subjective tax , and less of attention from people that want to pay the regional income tax.Keyword : Controlling, Collection regional income tax, Badan Pendapatan Daerah Pekanbaru City